A torre de Hércules e as emissões monetárias de D. Fernando I de Portugal na Coreunha - Centeno, Rui M. S. (2016)
Study of the rares half-torneses of King Ferdinand I of Portugal, minted in La Coruña with representation in reverse of the Roman lighthouse preserved in this Galician town. Based on the study of these coins it is proposed a new arrangement of all issues made by the Portuguese king in La Coruña.